2019
DOI: 10.1158/1078-0432.ccr-18-1941
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Extracellular Vesicles in Plasma from Glioblastoma Patients

Abstract: Purpose: Glioblastoma (GBM) is the most common primary brain tumor. The identification of blood biomarkers reflecting the tumor status represents a major unmet need for optimal clinical management of patients with GBM. Their high number in body fluids, their stability, and the presence of many tumor-associated proteins and RNAs make extracellular vesicles potentially optimal biomarkers. Here, we investigated the potential role of plasma extracellular vesicles from patients with GBM for diagnosis and follow-up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
139
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(181 citation statements)
references
References 53 publications
13
139
0
2
Order By: Relevance
“…When comparing EV concentrations over different time points, an increase in EV concentrations correlated with tumour recurrence, suggesting that exosomes could help to predict GBM recurrence. 120 Similarly, Andre-Gregoire et al 121 observed a higher concentration of EVs in patients with GBM, as well as showing that EVs from patientderived glioblastoma stem cells, which are thought to be involved in tumour initiation, expansion, resistance to treatments and relapse, had increased cargo relating to cell adhesion after TMZ treatment, indicating that TMZ had the potential to promote the increased release of factors favouring tumour progression. 121 Manda et al 124 123 Also, the presence of EGFRvIII in exosomes correlated with a lower overall survivor pattern-21.1 months-compared with 28.6 months for patients with no EGFRvIII expression in exosomes.…”
Section: Microvesicles In Glioblastomamentioning
confidence: 95%
See 1 more Smart Citation
“…When comparing EV concentrations over different time points, an increase in EV concentrations correlated with tumour recurrence, suggesting that exosomes could help to predict GBM recurrence. 120 Similarly, Andre-Gregoire et al 121 observed a higher concentration of EVs in patients with GBM, as well as showing that EVs from patientderived glioblastoma stem cells, which are thought to be involved in tumour initiation, expansion, resistance to treatments and relapse, had increased cargo relating to cell adhesion after TMZ treatment, indicating that TMZ had the potential to promote the increased release of factors favouring tumour progression. 121 Manda et al 124 123 Also, the presence of EGFRvIII in exosomes correlated with a lower overall survivor pattern-21.1 months-compared with 28.6 months for patients with no EGFRvIII expression in exosomes.…”
Section: Microvesicles In Glioblastomamentioning
confidence: 95%
“…The authors also concluded that GBM cells shed MVs, and that their contentthat included angiogenic proteins in addition to EGFRvIII-can enhance the angiogenic phenotype of normal brain endothelial cells and proliferation in other glioma cells. 119 Exosomes in glioblastoma Osti et al 120 demonstrated that the concentration of EVs was increased in GBM patients in comparison with healthy controls and patients with other CNS diseases. When comparing EV concentrations over different time points, an increase in EV concentrations correlated with tumour recurrence, suggesting that exosomes could help to predict GBM recurrence.…”
Section: Microvesicles In Glioblastomamentioning
confidence: 99%
“…Cortactin has been also implicated in release of extracellular vesicles (EVs) in the TME [98]. EVs are key messengers of intercellular communications that control the establishment and maintenance of TME [99], are actively secreted by GBM cells, and promote their oncogenic features [100][101][102][103]. For instance, GBM-secreted EVs stimulate recipient astrocytes to acquire a pro-tumoral phenotype by delivering several factors, including MYC and MYCN [101].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Characterizing the protein cargo of plasma EVs in patients with GBM and healthy controls through a MS-based proteomic analysis revealed a GBM-distinctive signature. These findings indicated that measurement of plasma EV concentrations together with the possibility to characterize their specific cargo can be of assistance in diagnosis, treatment, and follow-up of GBM patients [35].…”
Section: Evs In Glioblastomamentioning
confidence: 88%
“…Tumor-specific EVs were detected in a syngeneic mouse tumor model [49]. Osti et al [35] ( Table 1) analyzed plasma EVs (microvesicles) in preoperative GBM samples. EVs concentration significantly declined after resection of the primary GBM and raised with tumor relapse.…”
Section: Evs In Glioblastomamentioning
confidence: 99%